A review on risk-taking in tournaments. (10th May 2019) - Li, Zejun; Wang, Chengyuan; Wang, Qiong; Luo, Biao
Abstract : Purpose: This paper aims to summarize antecedents and consequences of risk-taking in tournaments and show the development of tournament optimization considering risk-taking. Moreover, further expansion expectations related to antecedents and consequences of risk-taking in tournaments and tournament optimization considering risk-taking are discussed. Design/methodology/approach: A comprehensive bibliographic retrieval and further literature review and systematics re-organization are used to build the framework with respect to risk-taking in tournaments. Then, qualitative analysis is used to present conclusions of existing research. Findings: By summarizing various antecedents, different consequences and tournament optimizations with regard to risk-taking in tournaments of existing research, the authors present a series of research opportunities regarding risk-taking in tournaments that can propel the advancement of tournament theory. Originality/value: The studies on risk-taking in tournament have been recently received wide attention and are growing vigorously. Based on the summary and re-organization, the framework of literature studying risk-taking in tournaments is built. This literature review also helps researchers learn the advance of risk-taking in tournament and provides fruitful direction for future research on this topic.